Male circumcision and prevalence of genital human papillomavirus infection in men: a multinational study - Albero, Ginesa (BioMed Central, 2013)
BACKGROUND: Accumulated evidence from epidemiological studies and more recently from randomized controlled trials suggests that male circumcision (MC) may substantially protect against genital HPV infection in men. The purpose of this study was to assess the association between MC and genital HPV infection in men in a large multinational study. METHODS: A total of 4072 healthy men ages 18–70 years were enrolled in a study conducted in Brazil, Mexico, and the United States. Enrollment samples combining exfoliated cells from the coronal sulcus, glans penis, shaft, and scrotum were analyzed for the presence and genotyping of HPV DNA by PCR and linear array methods. Prevalence ratios (PR) were used to estimate associations between MC and HPV detection adjusting for potential confounders. RESULTS: MC was not associated with overall prevalence of any HPV, oncogenic HPV types or unclassified HPV types. However, MC was negatively associated with non-oncogenic HPV infections (PR 0.85, 95% confident interval: 0.76-0.95), in particular for HPV types 11, 40, 61, 71, and 81. HPV 16, 51, 62, and 84 were the most frequently identified genotypes regardless of MC status. CONCLUSIONS: This study shows no overall association between MC and genital HPV infections in men, except for certain non-oncogenic HPV types for which a weak association was found. However, the lack of association with MC might be due to the lack of anatomic site specific HPV data, for example the glans penis, the area expected to be most likely protected by MC.